The Relation of Copping Strategy by Looking Social Support with Stress Level of Breast Cancer Patient who Gone Through Chemotherapy - Sri Burhani Putri; Achir Yani Syuhaemi Hamid; Vetty Priscilla (Elevate, 2018)
Background: Breast cancer is one of the most common illness that killed woman. One of the therapy to cure breast cancer is chemotherapy. Chemotherapy has side effect either physical and psychology, that caused people who’s in chemo therapy, prone to stress. Stress effected by many factors, such as characteristic and chopping strategy that patient has been using. Purpose: To get a perspective about the relation of characteristic and chopping strategy with breast cancer patient stress, whose in chemo therapy. Method: This research using cross sectional study and taking sample by using accidental sampling method. Results: The data analyzed by using bivariat and multivariat with variable result shows that breast cancer patient stress who has chemo therapy related to age characteristic (p value = 0.00) the time since they diagnosed with cancer (p value = 0.03), how long they have chemo therapy (p value = 0.00) and chopping strategy by looking social support (p value = 0.00) looking for spiritual (p value = 0.00) with dominant variable which related to stress is chopping strategy to looking spiritual support (coefficients B = -1.139).